1997
DOI: 10.2307/3433297
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette Smoke Radicals and the Role of Free Radicals in Chemical Carcinogenicity

Abstract: This article consists of two parts: a brief overview of the ways in which free radicals can be involved in chemical carcinogenesis, and a review of cigarette smoke chemistry. Carcinogenesis is generally agreed to involve at least three stages: initiation, promotion, and progression. It is suggested that radicals sometimes are involved in the initiation step, either in the oxidative activation of a procarcinogen (such as benzo[alpyrene) to its carcinogenic form or in the binding of the carcinogenic species to D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
69
1
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(75 citation statements)
references
References 71 publications
1
69
1
1
Order By: Relevance
“…5 The ocular surface is exposed to over 1E+14 short-lived radicals in the gas phase per puff and even more in the tar phase during which the radicals are long lived. 6 Altinors et al 7 assessed the lipid layer of the tear film in smokers and reported damage in the lipid layer which prevents the even spreading of tear film over the corneal surface, rendering it unwettable. According to them, smoking damages the precorneal tear film lipid layer by lipid peroxidation process and causes dry eye symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 The ocular surface is exposed to over 1E+14 short-lived radicals in the gas phase per puff and even more in the tar phase during which the radicals are long lived. 6 Altinors et al 7 assessed the lipid layer of the tear film in smokers and reported damage in the lipid layer which prevents the even spreading of tear film over the corneal surface, rendering it unwettable. According to them, smoking damages the precorneal tear film lipid layer by lipid peroxidation process and causes dry eye symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…7 Cigarette smokers also have higher levels of lipid peroxidation than non-smokers. 6 The chemical composition of cigarette smoke is complex, with many free radical species, aldehydes, peroxides, epoxides, nitrogen oxides, peroxyl radicals, and other pro-oxidants being present. 8 There is growing evidence that these oxidant species may contribute to the disease process associated with smoking.…”
Section: Discussionmentioning
confidence: 99%
“…Cigarette smoke is a complex mixture of thousands of constituents and induces the production of reactive oxygen species (ROS). Particulate tar and gas phase smoke component of CS also contain many semiquinone radicals, ROS and reactive nitrogen species (RNS) and carbon monoxide which have been associated with various chronic pulmonary and cardiovascular diseases ranging from inflammation to cancer [28]. GSH plays a major role in protecting biomolecules from oxidative damage caused by cigarette smoke.…”
Section: Discussionmentioning
confidence: 99%
“…A fairly recent study demonstrated a sharp drop in OPO activity after smoking a single cigarette in both non-smokers and smokers and suggested that reactive oxygen species (ROS), such as the hydroxyl radical, might cause oxidative DNA damage to the surrounding tissues (Pryor, 1997). In this respect, the saliva antioxidative system also contributes to anticarcinogenic capability.…”
Section: Introductionmentioning
confidence: 99%